2008
DOI: 10.1111/j.1538-7836.2008.02849.x
|View full text |Cite
|
Sign up to set email alerts
|

A viable mouse model of factor X deficiency provides evidence for maternal transfer of factor X

Abstract: Background:Activated factor X (FXa) is a vitamin K-dependent serine protease that plays a pivotal role in blood coagulation by converting prothrombin to thrombin. There are no reports of humans with complete deficiency of FX, and knockout of murine F10 is embryonic or perinatal lethal. Objective:We sought to generate a viable mouse model of FX deficiency. Methods:We used a socket-targeting construct to generate F10-knockout mice by eliminating F10 exon 8 (knockout allele termed F10tm1Ccmt, abbreviated as ‘−’; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Identical findings were observed in mice injected with doses of AAV-mFVIIa adequate to generate circulating mFVIIa levels of 300-800 ng/ml (6-16 nM), and overexpression of mFVIIa at levels greater than 2,000 ng/ml (40 nM) caused early mortality in both normal and hemophilic mice, with pathology predominantly in heart and lungs. We also demonstrated that crossing mFVIIa-overexpressing mice into a newly generated low-factor X (low-FX) mouse model (6) resulted in restoration of normal longevity and decreased thrombin generation, which indicates that the shortened lifespan of the high expressers is mediated through the coagulation cascade rather than another mFVIIamediated signaling event. These results establish ranges for hemostatic efficacy of continuously expressed mFVIIa in a mouse model and also define upper limits for safety for continuously expressed mFVIIa.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Identical findings were observed in mice injected with doses of AAV-mFVIIa adequate to generate circulating mFVIIa levels of 300-800 ng/ml (6-16 nM), and overexpression of mFVIIa at levels greater than 2,000 ng/ml (40 nM) caused early mortality in both normal and hemophilic mice, with pathology predominantly in heart and lungs. We also demonstrated that crossing mFVIIa-overexpressing mice into a newly generated low-factor X (low-FX) mouse model (6) resulted in restoration of normal longevity and decreased thrombin generation, which indicates that the shortened lifespan of the high expressers is mediated through the coagulation cascade rather than another mFVIIamediated signaling event. These results establish ranges for hemostatic efficacy of continuously expressed mFVIIa in a mouse model and also define upper limits for safety for continuously expressed mFVIIa.…”
Section: Introductionmentioning
confidence: 95%
“…These mice are F10 knockouts and knockins for a F10 variant based on a human FX (hFX) mutation (FX Friuli ; ref. 10) that results in low FX activity (~5.5%) in homozygous mice without affecting survival (6). The targeted knockin of the murine F10 Friuli allele (F10 tm2Ccmt ) allows expression of this variant from the endogenous promoter.…”
Section: Figurementioning
confidence: 99%
“…5 Animals expressing fII MZ developed cardiac fibrosis, worsening with age, similar to mice with low levels of tissue factor, fII, fVII, fX, and fXIII. 8,[28][29][30][31] Areas of fibrosis colocalized with areas of iron deposition, likely related to recurrent small hemorrhages. Unlike mice with low levels of fII (both fII lox/2 mice and transgenic mice expressing low levels of human prothrombin) that only develop modest cardiac fibrosis at over one year of age, 8 fII MZ mice developed substantial cardiac fibrosis by 8 to 10 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Similar hemostatic defects were observed in mice expressing very low levels of fVII (ϳ1%) and low levels of fX (approximately 5.5%). 4,6 In contrast, mice lacking either fVIII or fIX survive to adulthood and have no hemostatic defects in their hearts. However, patients with hemophilia A (fVIII deficiency) or hemophilia B (fIX deficiency) often experience spontaneous hemorrhages in tissues with low levels of tissue factor expression (ie, joints and skeletal muscle) and have excessive hemorrhage after injury.…”
mentioning
confidence: 99%